The Importance of Parental Involvement in the Learning Process at KB – TK Ibnu Sina - Jafar, Naurah Aqinah; Madinah, Maryam; Agustina, Nirmala Cahya; Renata, Nabila; Anggryani, Katarina Kurniawati; Unat, Chichie Inrirayu (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
Parental involvement in early childhood learning plays an essential role in supporting children’s educational success and overall development. This study aims to analyze the forms, factors, and strategies of parental involvement in learning at KB-TK Ibnu Sina. The method used is a literature study supported by observations and teacher interviews. The results show that parental involvement remains low despite the presence of a school committee as a collaborative platform. The lack of involvement is influenced by parents’ busy schedules and limited understanding of their role in their children’s education. Teachers play a crucial role in bridging communication between the school and parents through two-way communication and parenting programs. Implementing collaborative strategies can enhance parental participation, which positively impacts children’s motivation, confidence, and socio-emotional development. Keywords: parental involvement, early childhood, teacher role, school collaboration, learning.